2010
DOI: 10.1111/j.1349-7006.2010.01534.x
|View full text |Cite
|
Sign up to set email alerts
|

Y‐box binding protein‐1 is a novel molecular target for tumor vessels

Abstract: Y-box binding protein-1 (YB-1) is a member of the cold shock protein family and functions in transcription and translation. Many reports indicate that YB-1 is highly expressed in tumor cells and is a marker for tumor aggressiveness and clinical prognosis. Here, we show clear evidence that YB-1 is expressed in the angiogenic endothelial cells of various tumors, such as glioblastoma, esophageal cancer, gastric cancer, colon cancer, and lung cancer, as well as in tumor cells. YB-1 was highly expressed in glomerul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 32 publications
(57 reference statements)
0
25
0
Order By: Relevance
“…In addition, several genes important for wound healing and cellular proliferation and survival are regulated by YB-1, including collagen alpha1 and alpha2 (Norman et al 2001;Higashi et al 2003), matrix metalloproteinase 2 (Mertens et al 1997), the B-chain isoform of plateletderived growth factor (Stenina et al 2000), vascular endothelial growth factor (Coles et al 2004), granulocyte-macrophage-colony stimulating factor (Coles et al 2000), and Fas death receptor (Lasham et al 2000); moreover, YB-1 can also regulate αSMA and human pulmonary myofibroblasts (Zhang et al 2005). Takahashi et al (2010) reported that YB-1 is increased in the angiogenic endothelial cells of various tumors and is involved in the growth of endothelial cells. These previous findings suggest the possibility that YB-1 is involved in tissue regeneration in various situations in vivo, including tissue regeneration after ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several genes important for wound healing and cellular proliferation and survival are regulated by YB-1, including collagen alpha1 and alpha2 (Norman et al 2001;Higashi et al 2003), matrix metalloproteinase 2 (Mertens et al 1997), the B-chain isoform of plateletderived growth factor (Stenina et al 2000), vascular endothelial growth factor (Coles et al 2004), granulocyte-macrophage-colony stimulating factor (Coles et al 2000), and Fas death receptor (Lasham et al 2000); moreover, YB-1 can also regulate αSMA and human pulmonary myofibroblasts (Zhang et al 2005). Takahashi et al (2010) reported that YB-1 is increased in the angiogenic endothelial cells of various tumors and is involved in the growth of endothelial cells. These previous findings suggest the possibility that YB-1 is involved in tissue regeneration in various situations in vivo, including tissue regeneration after ischemic injury.…”
Section: Discussionmentioning
confidence: 99%
“…1), it seems very likely that overexpression of hPRDX4 in the atherosclerotic aorta protects against chronic inflammation and subsequent disease progression by preventing inflammatory cell-derived ROS generation and scavenging the generated extracellular pool of ROS. Indeed, we detected lower levels of 8-OHdG, oxLDL, and circulating TBARS as markers of oxidative stress (3,21,23) (Fig. 4), and reduced cellularity of macrophages as secretory cells in the fibrous caps of the atheromas (Supplementary Table S1) in HcD-fed hPRDX4…”
Section: Role Of Prdx4 In Atherosclerosismentioning
confidence: 99%
“…For the monoclonal mouse a-SMA antibody, we treated sections with the HistoMouse TM -Plus Kit (Invitrogen Corporation, Camarillo, CA) to block endogenous IgG. Double IHC was also performed to detect the distribution of both hPRDX4-and a-SMA-positive SMCs or both hPRDX4-and Mac-2-positive macrophages in atherosclerotic lesions (hPRDX4 with Vulcan Fast Red and a-SMA or Mac-2 with DAB as a substrate, respectively) using the MACH 2 Double Stain system (Biocare Medical) (3,23).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…The cell proliferation assay has been previously described. (17) Briefly, siRNA-transfected A110L cells were seeded into 12-well plates at a density of 1 · 10 4 cells per well. Twenty-four hours after transfection was set as time zero.…”
Section: Methodsmentioning
confidence: 99%